Determinants of digitization disclosure in IBEX-35 companies - Arias Abelaira, Triana; Rodríguez-Ariza, Lázaro; Pache Durán, María; Texeira Fernandes Justino, Maria do Rosário (Social responsibility journal, 2024)
Purpose Corporate digital responsibility is a challenge for companies as it recognizes that the use of technology can have a significant impact on society. In addition, a whole philosophy of nonfinancial disclosure has recently been developing and has become a priority for organizations seeking to be transparent and accountable. While some companies have already adopted this approach, practices related to information transparency in corporate digital responsibility are still in their early stages, creating a need to improve reporting and promote greater understanding in this evolving field. Based on a study analyzing the disclosure of information on digitization and taking into account that the board of directors is the body in charge of companies’ disclosure policy, the study aims to identify the factors that favor this disclosure. Design/methodology/approach As established by Ponce et al. (2022), IBEX-35 companies are Public Interest Companies subject to European and international regulations and are required to provide information on economic efficiency indicators and nonfinancial indicators. In relation to the proposed objectives, the aim is to analyze the possible factors that condition the degree of dissemination of information on digitization. To this end, a multiple linear regression of the dissemination index has been proposed following the works of Gil et al. (2018), Rodríguez-Ariza et al. (2014) and Briano-Turrent & Rodríguez-Ariza (2013). The estimation will be performed using the SPSS software (version 27). Findings The results show that the number of independent directors has a positive influence on the level of information disclosed by companies online. Conversely – and in line with previous studies – board size does not have a significant impact on the level of information transparency. Research limitations/implications This study has a few limitations that adversely impact the generalizability of the results. First, the subjective problem inherent in the rating and evaluation of information collected in the annual reports of sample companies cannot be excluded. Second, the consideration that each element that constitutes the IDT has the same weight, there being no weighting criteria. Finally, the study population is limited to 35 listed companies, not considering medium and small companies. Nevertheless, despite these limitations, the results are sufficiently interesting to justify and extend the research to a larger number of companies and, of course, to other stock market indices. Another interesting future line of research would be to include more independent variables to analyze what other factors determine the degree of digital transparency of companies. Practical implications The study may be useful for organizations to take into account when identifying the corporate governance characteristics that will improve the disclosure of information on digitalization, which is still incipient and voluntary. Similar considerations could be made with respect to the competent authorities in regulating the disclosure of information by companies, insofar as they should promote policies that, in general, favor corporate transparency. Originality/value This study contributes to the literature in three main ways: 1) although there is a large body of research that has explored the impact of corporate governance dimensions on the level of nonfinancial transparency, the present study pioneers the approach to digitalization disclosure in Spanish listed companies; 2) it provides evidence that it is highly advisable to have a majority of independent directors to achieve a higher degree of digital disclosure; and 3) the results of this research show the current state of digital transparency on the websites of most of the listed companies in Spain, which could serve as a benchmark for those responsible for issuing corporate governance policies and guidelines.